Learning to Straddle the Fence. - Hutchens, Myiah J. (Political Communication)
The author argues that practitioners of political communication and political campaign managers need several skills acquired in graduate school for maximum effectiveness in the 21st century. She discusses the growing influence of social media, pointing to the 2016 U.S. presidential election cycle, interpersonal communication, and the need for a basic understanding of computer programming and coding.